2020
DOI: 10.1007/s12471-020-01516-9
|View full text |Cite
|
Sign up to set email alerts
|

Sonothrombolysis in the ambulance for ST-elevation myocardial infarction: rationale and protocol

Abstract: Background Treatment of ST-elevation myocardial infarction (STEMI) has improved over the years. Current challenges in the management of STEMI are achievement of early reperfusion and the prevention of microvascular injury. Sonothrombolysis has emerged as a potential treatment for acute myocardial infarction, both for epicardial recanalisation as well as improving microvascular perfusion. This study aims to determine safety and feasibility of sonothrombolysis application in STEMI patients in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Furthermore, a substudy showed improved LV global longitudinal strain and decreased perfusion defect size by MCE at follow up, and the only independent predictor of LV remodeling was treatment with sonothrombolysis ( 106 ). As contrast ultrasound is portable, this technique was also shown to have a promising feasibility of in-ambulance sonothrombolysis for STEMI ( 107 ). These findings have provided more insight into the background of sonothrombolysis by contrast ultrasound and additional multi-center prospective studies are needed to test the clinical effectiveness of this method.…”
Section: Applications Of Mce In the Treatment Of Cmdmentioning
confidence: 99%
“…Furthermore, a substudy showed improved LV global longitudinal strain and decreased perfusion defect size by MCE at follow up, and the only independent predictor of LV remodeling was treatment with sonothrombolysis ( 106 ). As contrast ultrasound is portable, this technique was also shown to have a promising feasibility of in-ambulance sonothrombolysis for STEMI ( 107 ). These findings have provided more insight into the background of sonothrombolysis by contrast ultrasound and additional multi-center prospective studies are needed to test the clinical effectiveness of this method.…”
Section: Applications Of Mce In the Treatment Of Cmdmentioning
confidence: 99%
“…Ultrasound-guided thrombolysis is one of the most specific targeted tactics to improve thrombus dissolution. Previous studies have shown that the addition of sonothrombolysis before and after emergency PCI for acute STEMI can immediately improve microvascular flow (22,23). Microbubble cavitation induced by US has both catalytic and flow-inducing properties, and this approach takes advantage of these properties to create flow.…”
Section: Enhancing the Microcirculation By Using Better Techniquesmentioning
confidence: 99%
“…Intra-ambulance sonothrombolysis for STEMI has shown promising results in the first clinical trial (23), and the delivery of 3D-sono-assisted-thrombolysis in the ambulance may provide a convenient means of achieving rapid reperfusion while also treating microvascular injury and preventing systemic delays in the event of STEMI. The clinical feasibility and efficacy of 3D-sono-assistedthrombolysis in the treatment of STEMI in the clinical context need to be studied further.…”
Section: Prognosis and Future Directionsmentioning
confidence: 99%
“…With the emergence of this novel treatment, even portable ultrasound is going to be studied for safety and feasibility of sonothrombolysis in the ambulance between STEMI diagnosis and transfer to PCI center [ 33 ].…”
Section: Therapies To Prevent Distal Embolizationmentioning
confidence: 99%